Incidence Of Hemoglobinopathies In South Indian Population – 4 Year Study - A, Kavitha -; V, Kavita; ., Mukilarasi (Annals of Pathology and Laboratory Medicine, 2023)
Background Hemoglobinopathies are very common, but majority being asymptomatic it is under diagnosed. Hemoglobinopathies are important health care threat in tropical countries. The present study analyzed the incidence of hemoglobinpathies in south Indian population reported in regional laboratory in Chennai catering Tamil nadu and Andhra Pradesh population. Methods A cohort of samples which was received for abnormal hemoglobinopathy studies for evaluation of anemia and prenatal screening from Tamil nadu and Andrapradesh population for 4 years was analyzed using capillary electrophoresis method in (Sebia Minicap instrument) for incidence of hemoglobinopathies. Result Total number of cases studied during 4 years (2018-2022) is 17678, Of which 1194(7%) were detected with hemoglobinopathy/ abnormal hemoglobin variant. Of which 56.28% were female and 43.72% were male. Common age group under study is 21-30(30.07%). Beta thalassemia trait was detected at the highest frequency (69.13%) followed by HbE-Beta thalaseemia(6.87%) and least being HbD homozygous. Conclusion Our study analyzed a cohort and reported a spectrum of hemoglobin variants and its incidence in Tamil nadu and Andhrapradesh population.